(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2020)
With increased demand of quicker travel, both for passengers and cargo, there has been major advancements in commercial airlines and number of flights have increased significantly over the last few years. Novel challenges have been introduced due to the rising number of flights in the areas of safety, route planning and maintenance. In addition, for commercial flights, the surge in the number of passengers have also exposed avenues for improving the quality of flight travel, from entering the airport premises to leaving the same at the destination. Although there are many areas of flight and airport operations that can benefit from leveraging technological advancements, choosing safe flight path and making dynamic modifications to it is the critical aspect that needs to be addressed. Comprehending available information to adhere to the provided route and also avoiding known areas of air turbulence, adds to the financial benefit of the commercial airline as well as the safety of the airplane and the passengers are ensured. In this paper, the various aspects of improving the flight routing by providing dynamic intelligent path options to ensure adherence to the provided flight path possible is studied; options for improving the flight safety and turbulence avoidance, which benefits both the passengers and the aircraft are also explored. In addition, keeping aircraft away from conflict zones or war zones, and also from areas of natural disaster, like erupting volcanic ash or forest fires is relevant. Although these issues have been studied before, most of the techniques depend heavily on infrastructure that is on the ground. The basic model requires constant communication with an air traffic control tower, that would provide updates and changes to the flight path as necessary. This leads to some of these methods being unusable on flights operating on oceanic routes and away from the communication zone of the devices placed on land masses. Therefore, in this paper an Internet of Things based framework is proposed to address and handle the above mentioned issues. The framework is structured on the communication model of information exchange among aircraft within the range, as well as taking advantage of ground infrastructure if there is a possible network link to the same. A number of algorithms are proposed for dynamic intelligent routing of flights as well as detection and avoidance of air turbulence. The implementations of the proposed algorithms show improvements ranging from 10% to 30% in the methods as compared to using the infrastructure based conventional techniques.